Acceleration based manoeuvre flight control system for unmanned aerial vehicles - Peddle, Iain K. (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Electrical and Electronic Engineering))--Stellenbosch University, 2008.